Asset Management and Governance – An Analysis of Fleet Management Process Issues in an Asset-Intensive Organization - Mardiasmo, D.; Tywoniak, Stephane; Brown, Kerry; Burgess, K. (Institute of Electrical and Electronics Engineers ( IEEE, 2008)
Efficient asset management is a key performance driver for asset-intensive organizations. Achieving high utilization and return on investment on physical assets are central corporate objectives for public and private organisations alike. Current approaches on asset management include the engineering and governance perspectives. The engineering perspective on asset management concentrates on the technical and operational dimensions of asset performance, including utilization, and operation to technical specifications. However, this perspective often ignores organisational-level factors that potentially affect asset performance. By contrast, from a governance perspective, key factors influencing asset management performance include stewardship, accountability and incentive regimes. Symmetrically, the governance view often takes the operational factors for granted. In sum, both perspectives offer valuable but incomplete insights on the management of asset performance: experience demonstrates that an exclusive focus on one or the other may lead to sub-optimal asset and organizational performance. In this paper, we investigate how an integrated approach to asset management can be constructed in the context of vehicle fleets. Vehicle fleets provide a suitable context to investigate these issues as they constitute significant investments, and are observable across a range of asset-intensive industries. Beginning with an analysis of how the asset management process is operated through the asset lifecycle, we identify key engineering and organizational factors influencing asset performance. The relationships between factors are analyzed to provide an integrated fleet asset management approach.